Assessment of the urinary bladder prior to cesarean delivery in women with multiple abdominal scars through operation table ultrasonography: a case report - Laura-Christin Fangmann, MD; Wolfgang Henrich, MD, PhD; Larry Hinkson, MBBS, MRCOG, FRCOG, MD (Elsevier, 2023)
Bladder injury is a rare but serious complication that can occur during cesarean deliveries with an incidence of between 0.25% and 0.9%. Most bladder injuries (53%) occur upon entering the peritoneal cavity as a consequence of either extensive adhesions, a distorted pelvic anatomy, or an unexpectedly high-situated bladder owing to previous operations including a previous cesarean delivery. Patients with a previous abdominal operation can benefit from a preoperative ultrasound to identify the upper limits of an unexpectedly enlarged urinary bladder, even after preoperative catheterization. A modified surgical approach can then be applied to allow entry into the peritoneum above the bladder, thus preventing severe bladder injury. Surgeons may consider the use of preoperative sonography before operating on women with a previous abdominal surgery, especially following midline incisions, to improve safety and to potentially modify abdominal entry into the peritoneal cavity to avoid bladder injury.